Cerebrovascular Complications in Pediatric Patients with COVID-19 Infection - Chaudhry, Thymur Ali; Palabiyik, Figen; Moum, Sarah J. (Journal of Pediatric Neurology, 2022)
Since the onset of the coronavirus disease 2019 pandemic, a variety of neurological manifestations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported in patients, of which one of the most concerning is stroke. This review aims to summarize the current literature and evolving understanding of pediatric cerebrovascular complications in the setting of SARS-CoV-2.
Keywords: pediatric stroke; SARS-CoV-2; cerebrovascular complications